2018
DOI: 10.1016/j.sdentj.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of white spot lesion: Maxilla and mandibular teeth

Abstract: The material produced favorable esthetics on colour and the surface roughness of teeth at distinct treatment times. It is recommended to be used to improve WSL post orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…The L*, a*, and b* values used in the present study is a quantitative index of color enacted by the Commission International de l'Eclariage (CIE) 1978. 45 Additionally, SEM was performed to observe both the surface and cross-section microstructures of enamel to obtain more morphological details.…”
mentioning
confidence: 99%
“…The L*, a*, and b* values used in the present study is a quantitative index of color enacted by the Commission International de l'Eclariage (CIE) 1978. 45 Additionally, SEM was performed to observe both the surface and cross-section microstructures of enamel to obtain more morphological details.…”
mentioning
confidence: 99%
“…The L parameter represents the color's lightness [40]. Many studies have shown that creating the wsl raises the whiteness of the tooth by affecting the absorbing light in that region, implying the treatments' influence on the teeth's brightness [41]. In comparison to the peptide group, our findings show that the groups F-LLLT and BAG had a significant reduction in tooth color.…”
Section: Discussionmentioning
confidence: 55%
“…On the tooth treated with the abrasive erosion technique, the surface underwent heterogeneous abrasion on which a surface layer persisted without any type of etching pattern that would allow the infiltration by any type of resin (Figure 18). As in other studies [41,46,47,49], both teeth were analyzed under an electronic microscope in order to examine the surface characteristics produced by the chemical erosion and abrasive erosion processes. We observed that the tooth treated with chemical erosion presented an etching pattern with complete erosion at the centers of the enamel prisms.…”
Section: Discussionmentioning
confidence: 99%